Phytochemical Properties and Antimicrobial Susceptibility Testing of "Gegemu" (Datura stramonium) Leaf Extract on Bronchitis Causing Organisms (Lafia Journal of Scientific and Industrial Research, 2026)
This research was carried out to determine the phytochemical components of “gegemu” (Datura stramonium) and its antimicrobial susceptibility on bronchitis causing organisms: Staphylococcus aureus, Streptococcus pneumonia, Klebsiella pneumonia and Haemophilus influenza. Phytochemical analysis of aqueous, methanoic and ethanoic extracts of “gegemu” leaf was done. Kirby Bauer Disk diffusion method was used to determine the antimicrobial activities of aqueous, methanoic and ethanoic extracts of “gegemu” leaf. Minimum inhibitory concentration of the extracts against the bacterial isolates was determined. Phytochemical components of the test plant showed the presence of Steroid, Alkaloids, Phenols, Tannins, Flavonoid, Saponin, Terpenoid, Anthocyanin and Anthraquinone. Among the solvents tested, methanol was the best solvent for extracting the bioactive compounds of “gegemu” leaf. Methanoic extract had bactericidal activity against Staphylocococcus aureus at 23.5mg/dl as against the control, 27.5 mg/dl, 21mgldl; 29mg1dl for Streptococcus pneumoniae, 18.5mg/dl, 26.5 mg/dl for Klebsiella pneumonia and 19mg/dl, 25.5mg/dl for Haemophilus influenza. Conclusively, “gegemu” extract had proven to possess antibacterial activities against the test organisms. The study recommends among others, that a further research be directed toward isolating and characterizing the specific bioactive compounds in Datura stramonium responsible for its antimicrobial properties to better understand their mechanisms of action.